(untitled) (CIPEEX, 2025)
The principle of effectiveness, cited by Carlos Santiago Nino in 1993, highlights the importance of ensuring that legal rules are applied effectively, producing practical results. In this context, automation emerges as a potentially effective tool for achieving the CNJ’s goals for the Brazilian Judiciary. This paper aims to explore this relationship and analyze the impact of automation on judicial activities. Faced with the current scenario of the Brazilian Judiciary, characterized by challenges such as procedural slowness and lack of access to justice, the following question arises: How can automation be an effective tool for achieving the CNJ’s goals for the Judiciary? The general objective of this research is to analyze how automation can be an effective instrument for achieving the goals set by the CNJ for the Brazilian Judiciary. The following specific objectives were formulated: i) to discuss the doctrinal concept of the principle of effectiveness, highlighting its importance in the Brazilian legal context; ii) to address the legal provision of the principle of effectiveness in the Brazilian legal system, contextualizing its application in judicial activities; iii) to analyze how automation can be used to promote procedural agility, access to justice, transparency and cost reduction in the Judiciary. The methodology of this study will include the analysis of news published on the CNJ website, as well as consultation of the article "Automation improves the monitoring of the National Goals of the Judiciary" by Margareth Lourenço. In addition, research will be carried out on legal and academic databases to support the theoretical and practical discussion on the subject. This project is justified by the relevance of the topic and the need to find solutions to the challenges faced by the Brazilian Judiciary. Automation has emerged as a promising alternative for improving the efficiency and effectiveness of judicial activities, contributing to improving access to justice and promoting faster and more transparent justice. It is hoped that this study will be able to identify and analyze the main impacts of automation on judicial activities, providing support for an understanding of how this tool can be an effective instrument for achieving the CNJ’s goals for the Brazilian Judiciary. In addition, it is hoped that this research can contribute to the development of proposals and strategies for the implementation of automation in the judicial system, with the aim of improving its efficiency and promoting a more accessible and democratic justice system.